Representation of the concept Evaluation in the paremiology of the Kazakh and English languages - Duisekova, К.К.; Dautbayeva*, Қ.Б. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
The article deals with the ethnolinguistic and cognitive aspects of the Kazakh and English proverbs and sayings. The comparative approach to the analysis of the proverbs and sayings allows to determine their national and cultural peculiarities and study the problem of reflecting the concept of evaluation in the paremiological system of the above-mentioned languages.The authors interpret the paremiological material as the language fund which includes short and set expressions, usually rhythmically organized, sometimes directly or indirectly transmitted parables, etc. These expressions accumulated by the centuries through the experience of the people help to determine the place and the role of the concept of evaluation in the field of paremiology of the Kazakh and English languages. The present article also gives a detailed analysis of the concept and its semantic structure that has become one of the main notions of cognitive linguistics. The concept of evaluation constituting a part of the world`s value system is reflected in the representational value system of each ethnos and bears idioethnic features in the Kazakh and English languages that differ basically in their structure and genetically.